Ethno-Stem Project-Based Learning: Its Impact to Critical and Creative Thinking Skills (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Guiding students how to think critically and creatively is a crucial part of the educational process in order to meet the required skills to face the 21st century. In addition, attention to the local culture especially that is closely related to the scientific concepts needs to be strongly emphasized. Due to those two aspects i.e. creative and critical thinking as well as attention to local culture, the ethno-STEM project-based learning for high school students has been implemented and its impact to students’ critical and creative thinking skills has been investigated. This study involved 230 students from seven high schools in Central Java Indonesia. The data collection was carried out through a set of instruments to reveal the students’ critical and creative thinking skills. The instruments were declared as valid based on the experts’ judgment and showed an Alpha Cronbach score of 0.79 prior to use. The results showed that the ethno-STEM project-based learning was able to improve the average critical and creative thinking skills of students in all indicators varying from low to medium categories. The improvement of students' critical thinking skills was observed by the achievement of the N-gain score, i.e. 52 students (22.6%) achieved a high category, 102 students (44.4%) achieved a medium category, and 76 students (33.0%) achieved a low category. Moreover, an increase in the creative thinking skills was also observed, indicated by the N-gain score, i.e. 63 students (27.4%) were at a high category, 109 students (47.4%) were at a medium category, and 58 students (25.2%) were at a low category. In conclusion, the ethno-STEM project-based learning showed a significant effect on the improvement of students' critical and creative thinking skills.